Distribución espacial y aspectos ecológicos de Neostrengeria macropa (Decapoda: pseudothelphusidae) en la Sabana de Bogotá, Colombia (2017)
"The pseudotelfusidos crabs are part of the aquatic fauna of mountain ecosystems of central and southern America. Many of them have marked endemism and are determinant to know their distribution and ecological. Neostregeria macropa (H. Milne-edwards, 1853), is an endemic crab from the Savannah of Bogotá, cited in the red lists of species in vulnerable states and danger of extinction. For this reason, the distribution of ecological potentials of N. macropa, using an ecological niche model, was established and evaluated using the presence data of the species in the Bogotá savanna, the environmental variables of Word-Clim and the programs MaxEnt, R main team, with the statistical package Dismo and Arcmap". -- Tomado del Formato de Documento de Grado.